ENCEPHALOPATHY REMAINS A CURRENT PROBLEM IN MEDICINE - Yangibaev Jonibek Saparbaevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Prevention and treatment of cerebrovascular diseases remain one of the most urgent and unresolved issues in clinical neurology. First of all, this concerns dyscirculatory encephalopathy, the relevance of which is due to the prevalence of the disease and polymorphic clinical manifestations. Dizziness, headache, memory loss, fatigue, sleep disturbance - this is not a complete list of initial symptoms that reduce the quality of life of a person, make it difficult to adapt to increased psycho-emotional and physical stress, making it impossible or difficult to continue professional activities.